P145: HIV point of care testing by community paramedics in a vulnerable population: a pilot study. (2nd June 2016) - Yaworski, H.; Hutlet, P.; Grierson, R.; Weldon, E.; Sneath, R.; Kasper, K.; Becker, M.; Pindera, C.; Carnochan, T.
Abstract : Introduction: Literature suggests that up to 25% of people with HIV in North America are unaware of their status and are at risk to transmit the virus unknowingly. A high proportion of HIV patients are diagnosed when the disease is more advanced, with CD4 counts < 200. This study examined the rates of HIV testing, detection, and treatment of clients at an inner city shelter and detoxification centre after the introduction of a point of care testing (POCT) program by on-site community paramedics (CP).Methods: In 2013, in collaboration with a regional HIV program, CP received training and instituted an HIV POCT program and post-test counselling initiative. A retrospective electronic database review from October 16, 2013 to October 15, 2014 of adult patients who received testing was performed. Demographic and testing details of each patient encounter were abstracted and select variables were compared to a historic population who received POC HIV testing at an inner city emergency department (ED) in the same city.Results: 1, 207 HIV POC tests were performed on 997 patients during the pilot. 57% of the patients tested were less than 40 years of age (range 18-73 years) compared to 55% in the historic ED population. A total of 9 reactive cases were identified in the study population including 3 new cases, 5 previously known cases, and 1 false reactive result. The mean age of the new cases was 47 years, vs 44 in the historical control. All 3 new cases were referred to a local HIV clinic for further care and treatment. New HIV cases represented 0.25% of total tests performed, which is less than the expected prevalence rate of 1% for this population, as well as the rate of 1.4% found in the ED population.Conclusion: Despite lower than expected reactive rates, the large scale implementation of a CP HIV POCT program in an inner city shelter and detoxification centre is feasible. All patients with new reactive tests were immediately connected to care. Future research will focus on risk factors and barriers to testing.